Exploring Female University Students' Participation in Physical Activity in Saudi Arabia: A Mixed-Methods Study - Aljehani, Najla; Razee, Husna; Ritchie, Jan; Valenzuela, Trinidad; Bunde-Birouste, Anne; Alkhaldi, Ghadah (Frontiers in Public Health, 2022)
Background The importance of physical activity in improving physical and mental health has been emphasized in many studies. Researchers in Saudi Arabia have reported an increase in physical inactivity among Saudis, especially among University female population. Current efforts in the field in Saudi Arabia have yet to explore barriers and facilitators that influence female University student's participation in physical activity. This study aims to provide an assessment of the situation regarding physical activity among female University students in Saudi Arabia. Methods This mixed method study preceded a participatory action research initiative. The first part of the mixed method consisted of a cross-sectional survey of 375 female University students in Saudi Arabia who completed the short form of the International Physical Activity Questionnaire. The second part consisted of semi-structured, in-depth interviews with 14 female University students and 16 female exercise trainers. Results Results showed that most participants (91%) spent more time in walking activity compared to moderate (66%) and vigorous activity (57%) for at least 10 min at a time over a period of 7 days. Results showed that 70% of participants did not meet the WHO recommendation of 150 min per week of moderate activity, while around 62% of participants did not meet the WHO recommendation of 75 min per week of vigorous activity. Barriers to participation included limited facilities for physical activities, academic workload, gender role, and the need to adhere to cultural standards. Facilitators included valuing positive results, general health concerns, and family support. Conclusion Knowledge gained from this study might support organizations and public health authorities to develop physical activity interventions that better address Saudi women's perceived needs. These findings are an important contribution to current knowledge in light of recent advances in women's rights in Saudi Arabia.